MEMBRAN Zirconia.titania UNTUK PENGOLAHAN AIR LIMBAH: KAJIAN LITERATUR - Familia Novita Simanjuntak; Ngia Masta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
The need for clean water is a necessity to sustain human life. This need will continue increasing in line with the human population growth, but it is not balanced by appropriate wastewater treatment to preserve the clean water stock. Zirconia and titania-based membrane technology is a promising technology in water and waste treatment processes because it is able to produce a good and stable quality of water against chemical reactions, high temperatures, and mechanical stress. This study aims to literature study-based analyze the capability of synthesis, characterization, and application of a membrane that combines zirconia and titania (Zr1-xTix)O2 with Al2O3 as a substrate for domestic wastewater treatment. The discussion describes the method of zirconia.titania membrane application to support its performance in domestic wastewater treatment.